Economic impact of high-yielding cassava (Manihot esculenta) varieties in Tamil Nadu: Insights on farmer adoption and preferences - PRAKASH, P; JAGANATHAN, D; IMMANUEL, SHEELA (The Indian Journal of Agricultural Sciences, 2025)
The study was carried out during 2022–23 in Salem, Tiruchirappalli, Namakkal, Cuddalore, Dharmapuri and Pudukkottai to examine the socio-economic impact of cassava (Manihot esculenta Crantz) production in Tamil Nadu, India based on a survey of 300 farm households. We employed cost-benefit analysis, propensity score matching and a logit regression model to assess the profitability of high-yielding cassava varieties (HYVs) and determine the factors influencing their adoption. Adoption rates were 47.31%, resulting in a 13% increase in yield and a 17% increase in income compared to local varieties. Factors driving adoption of HYVs included higher yield (ME=0.025), technical advice (ME=0.188) and irrigation, with drip (ME=0.193) and flood irrigation (ME=0.394). Farmers reported income growth as the primary motivation, followed by reinvestment in agriculture and loan repayments. The Sree Athulya variety was found to yield the highest net income/hectare. Key challenges included reliance on intermediaries and labour-intensive harvesting. Farmers preferred traits such as high yield, pest resistance, short duration, and drought tolerance. Promoting HYVs can boost the cassava sector and contribute to Sustainable Development Goals, driving economic prosperity and sustainability in the region.